PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN PADA PENGGUNA GRABBIKE DI MASYARAKAT - Rajmadivara, Caren Beautisyarof; Aulia, Zahra Aufa; Teosius Simaremare, Gold Friend; Rosento, Rosento (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
One of the most rapidly expanding industries in the modern digital age is online transportation services. The purpose of this research is to find out how much of an impact service quality has on GrabBike customer loyalty. Dependability, responsiveness, assurance, empathy, and concrete proof are the five main criteria used to evaluate service quality. Data was gathered using a quantitative research technique, with 100 respondents being polled using questionnaires. All responses were evaluated using a Likert scale ranging from 1 to 5. The findings demonstrate that customer loyalty is positively and significantly impacted by service quality. A simple linear regression test confirmed this, with a t-value of 8.292 surpassing the t-table value of 1.987 and a R Squared value of 41.2%. This indicates that service quality influences customer loyalty to a lesser extent than other criteria (58.8% vs. 41.2%). These results stress the need of enhancing service quality as a means of attracting and retaining customers, and they call for ongoing innovation to make online transportation services more user-friendly.